2009
DOI: 10.3109/09637480701830404
|View full text |Cite
|
Sign up to set email alerts
|

Iron absorption from brown rice/brown rice-based meal and milled rice/milled rice-based meal

Abstract: Iron absorbed from milled rice and brown rice did not differ significantly, as well as that from brown rice-based meal and milled rice-based meal. Differences in iron absorbed from brown/milled rice and brown/milled rice-based meals may be due to the iron content of the test foods and the presence of iron enhancers in the meal (e.g. fish, vegetables and citrus fruit).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
2
8
1
Order By: Relevance
“…These values agreed with earlier findings by Trinidad, et al [29] who found a range of 1.40 to 1.79 mg/100 g and 1.97 mg/100g reported by Tinsley and Emeritus [28]. The bran and the germ in brown rice contain many vitamins and minerals contributing to MCBR having the highest zinc content.…”
Section: Mineral Compositionsupporting
confidence: 82%
“…These values agreed with earlier findings by Trinidad, et al [29] who found a range of 1.40 to 1.79 mg/100 g and 1.97 mg/100g reported by Tinsley and Emeritus [28]. The bran and the germ in brown rice contain many vitamins and minerals contributing to MCBR having the highest zinc content.…”
Section: Mineral Compositionsupporting
confidence: 82%
“…Large particle size and high extraction resulting from milling, especially milling that involves a single pass through a stone mill, also can affect the bioavailability of iron, zinc, and calcium (58)(59)(60)(61). (This may be especially true for hard wheats, which are less well crushed using stone milling techniques.)…”
Section: Impact Of Different Milling Processes On Nutrientsmentioning
confidence: 99%
“…Most of the human intervention studies were acute in nature, with 5 studies related to assessment of postprandial glycaemic response [ 37 , 43 , 44 , 45 , 46 ], one on satiety [ 47 ] and two on iron absorption from single meals containing whole grains [ 48 , 49 ]. Two of these studies did not draw comparisons between the acute physiological impacts of rice consumption to non-whole grain comparators [ 37 , 49 ]. Only one of the five studies that compared glycaemic response of wholegrain foods to refined grain comparators studies suggested that whole grains blunted the postprandial glucose response [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two of these studies did not draw comparisons between the acute physiological impacts of rice consumption to non-whole grain comparators [ 37 , 49 ]. Only one of the five studies that compared glycaemic response of wholegrain foods to refined grain comparators studies suggested that whole grains blunted the postprandial glucose response [ 49 ]. One study [ 43 ] focused on (commercially-available, whole, multi-grain and refined grain) breads while the others compared whole and refined rice.…”
Section: Resultsmentioning
confidence: 99%